EFISIENSI SEKOLAH MENENGAH KEJURUAN (SMK) DI KOTA PEKANBARU - Sumarno ' (Jurnal Pendidikan, 2014)
This study aims to assess the efficiency of vocational schools in the city ofPekanbaru and find alternative ways of improving it. The study was conducted in 30 publicand private vocational schools are taken by clusterpurposive sampling. Data collected bydocumentation, questionnaires, and interviews technique from education authorities,schools, alumni, and DUDI. Data were analyzed by descriptive, correlation, ratios, andcomparison. The results showed that the SMK in the city of Pekanbaru is still not efficientbased on sources /uses of funds, the ratio of the unit cost to: the UN, the waiting period, andthe the first salary/income of graduates.Key words: School efficiency, vocational school.